Broadband noncollinear optical parametric amplifier using a single crystal. - Wasylczyk, P; Walmsley, I; Wasilewski, W; Radzewicz, C (2005)
A noncollinear optical parametric amplifier in which blue pump pulse generation as well as parametric amplification takes place in the same nonlinear crystal is presented. Broadband spectra tunable throughout over 100 nm in the visible were generated in a simple setup. The green output pulses were compressed to 65 fs, and efficiency (IR-to-visible) of 1.8% was achieved.